Epigenetic Control of Cell Division and Cell Differentiation in the Root Apex - Takatsuka, Hirotomo; Umeda, Masaaki (Frontiers in Plant Science, 2015)
Epigenetics is defined as heritable changes in gene expression and genome integrity that are accompanied by no alteration in DNA sequence. Throughout plant life cycle, many processes, including genome imprinting, stress responses, and cellular differentiation, are known to be determined by epigenetic regulation. The root apex is also considered to be under the control of epigenetic regulation for optimal growth under variable environments. Recent reports reveal that epigenetic control is especially important in the stem cell niche (SCN) and the meristematic zone (MZ) where both cell production and cell specification occur. DNA methylation, histone methylation and histone acetylation are well-known epigenetic modifications, and each epigenetic modification has distinct roles in roots. Here, we review the updated findings that demonstrate the significance of epigenetic regulation in root apex of Arabidopsis.